Implementasi Sumbang Duo Baleh Dalam Membentuk Etika Siswa Kelas IV di SDN 03 Pakan Labuah - Mitia, Rihan; Charles, Charles (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
Minangkabau culture has always been very concerned about manners and ethics, but over time these ethics and manners have faded with the times and the hope is that Minangkabau culture will not fade with time, therefore it is necessary to prevent this by applying duo baleh donations in Minangkabau, especially to children. This research method uses a qualitative approach. This type of research also uses library research or library research and an ethnographic approach. There are 12 baleh duo contributions, namely: Sitting Contrast, Tagak Contribution, Silent Contrast, Road Contribution, Kato Contribution, Caliak Contribution, Clothing Contrast, Karajo Contribution, Tanyo, Jajek Contribution, Bagaua Contribution, and lastly Kureanah Contribution. The solution to reducing deviant behavior is to provide a role model for children from parents, teachers, the community, and the surrounding environment and provide children with an understanding of donating duo baleh